Comparative analysis of efficacy of different combination therapies of α-receptor blockers and traditional Chinese medicine external therapy in the treatment of chronic prostatitis/chronic pelvic pain syndrome: Bayesian network meta-analysis. - Kaiyu Zhang; Yi Zhang; Shengwei Hong; Yutian Cao; Chengjiang Liu (PLoS ONE, 2023)
Background Combination therapy of α-receptor blockers (α-RBs) and traditional Chinese medicine external therapy can serve as a treatment of chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS). α-RBs includes tamsulosin, terazosin and so on and the traditional Chinese medicine external therapy includes needling, moxibustion, acupoint catgut embedding, acupoint application, auricular point sticking and hot medicated compress and so forth. Currently, there is no study in which Bayesian network meta-analysis is applied to making a comparative analysis of efficacy of different combination therapies of α-RBs and traditional Chinese medicine external therapy in the treatment of CP/CPPS. Therefore, based on Bayesian algorithm, a network meta-analysis was conducted by us to make a comparison between different combination therapies of α-RBs and traditional Chinese medicine external therapy. Methods A document retrieval was conducted in the databases PubMed, Cochrane Library, Embase, Web of science, China National Knowledge Infrastructure, WanFang Data Dissertations of China database, VIP China Science and Technology Journal Database, SinoMed. Literatures were searched for published in biomedical journals concerning clinical study on α-RBs combined with various traditional Chinese medicine external therapies in the treatment of CP/CPPS from inception of database to July 2022. Newest version risks of bias assessment tool (RoB2) was used to assess the risks of bias of studies included in this analysis. Stata 16.0 software and R4.1.3 software were used to make a Bayesian network meta-analysis and charts. Results 19 literatures were included involving 1739 patients concerning 12 interventions which were used in the treatment of CP/CPPS. With respect to the total effective rate, α-RBs+ needling was most likely to be the optimal treatment. Concerning National Institutes of Health Chronic Prostatitis Symptom Index (NIH-CPSI) total score, α-RBs+ moxibustion+ auricular point sticking was most likely to be optimal treatment, the therapy ranking second was α-RBs+ needling, and the therapy ranking third was α-RBs+ moxibustion. Pain score, voiding score and quality-of-life score are subdomains of the NIH-CPSI total score. With regard to pain score, α-RBs+ moxibustion was most likely to be optimal treatment. In reference to voiding and quality-of-life score, there was no statistically significant difference between the efficacy of various interventions. Conclusions α-RBs+ needling, α-RBs+ moxibustion and α-RBs+ moxibustion+ auricular point sticking provided relatively good efficacy in the treatment of CP/CPPS. In these treatments, attention should be paid on α-RBs+ needling and α-RBs+ moxibustion which ranked higher many times in the evaluation of various outcome indicators. However, there still were certain limitations in this study, so large-sample clinical randomized control trials with a rigor design following the evidence-based medicine standards need to be conducted to justify the results of this study. Systematic review registration [https://www.crd.york.ac.uk/prospero/], identifier: [CRD42022341824].